The Influence of Problem Based Learning and Discovery Learning Models on Student Learning Outcomes on Chemical Bonding Material - Sinaga, Tawarina Dameria; Tarigan, Simson (Indonesian Journal of Advanced Research, 2024)
The aim of this research is to find out how the Problem Based Learning and Discovery Learning learning models differ on student learning outcomes on chemical bonding material.. From the results obtained, namely tcount>t table (5.63<1.66). From the results of the average posttest score compared with the average KKM score for chemistry subjects, there is a significant influence of the Problem Based Learning learning model on student learning outcomes in chemical bonding material, namely (87.5 > 75), and there is also a significant influence Discovery Learning learning model on student learning outcomes in chemical bonding material, namely (81.29>75). And based on the posttest scores, namely (87.5> 81.29), the learning outcomes of students in the Problem Based Learning learning model on chemical bonding material were higher than the learning outcomes of Discovery Learning on chemical bonding material.